Pengembangan Kualitas Pelayanan Publik di Daerah - Desi Fernanda (Jurnal Administrasi Publik, 2003)
The Objective of Local Government is mainly to provide basic services in order to improve local community wellbeings. In Indonesia, the local government apparatus do not understand well about the issue of quality services, as they primarily give more attention on the issue of local revenues, based on local taxation and retribution. This has resulted in quality of services provided by most local authorities, that local community can hardly satisfied. With regards to such condition, the writer reccommends the local government to improve their quality of public services by establishing standards of quality public services and develop the capacity of local government aparatus to implement and to maintain excellences in the provision of local public services. In order to do that, the local governments need to understand the concept of excellence in public service, the principles in developing Minimum Standards of Public Services, and the model of quality services gaps.“With service excellence, everyone wins.Customers win. Employee win. Management wins.Stockholders win. Community win. The Country Wins.”(Zeithaml et.al.,1990: 2)